Treating Schizophrenia: Novel Targets for the Cholinergic System - Money, T.T.; Scarr, E.; Udawela, M.; Gibbons, A.S.; Jeon, W.J.; Seo, M.S.; Dean, B. (CNS & Neurological Disorders - Drug Targets, 2010)
Cognitive deficits in patients with schizophrenia are the biggest obstacle to achieving an independent and productive lifestyle, with these deficits being refractory to current drug treatments. Significantly, both nicotinic and muscarinic receptors (cholinoceptors) have been shown to have an important role in cognition and are therefore viewed as potential therapeutic targets for drugs designed to lessen cognitive deficits. Importantly, the demonstration that acetylcholinesterase inhibitors, which result in higher synaptic levels of acetylcholine, can reduce the cognitive deficits of schizophrenia suggested that under-stimulation of cholinoceptors could be associated with the cognitive deficits associated with this disorder. This has lead to a focus on the development of receptor agonists, partial agonists and allosteric agonists that can be used to stimulate cholinergic pathways and thus reduce the cognitive deficits of schizophrenia. In addition, muscarinic receptors have now been associated with the modulation of dopamine and may constitute an alternative target for the treatment of psychoses. Given these exciting new therapeutic initiatives, this review will outline current evidence that involves the cholinoceptors in the pathophysiology of schizophrenia and how these data can inform on approaches to more targeted treatments for the disorder.
Keywords: cognitive deficits